Egressos de cursos de graduação a distância da Universidade Federal de Minas Gerais: uma avaliação dos processos formativos e da trajetória profissional - Thiago Belchior Pinto (2020)
The present research aimed at investigating the perceptions from graduates from five undergraduate courses offered in the modality of distance learning by Federal University of Minas Gerais (UFMG), identifying data about the quality of the training, the teaching-learning process, and the insertion of those graduates in the work market. The egresses from distance learning (DL) are fundamental subjects to understand the relationship and the organizational structures inherent to this modality. They also help in understanding the dynamics of the teaching-learning process, and the teacher-student relationship in order to the disentagle the different pedagogical premises of DL.Thus, we consider the trajectory and the experience gathered by those graduatesduring their learning process a valuable source of information that can contribute to the processes of institutional evaluation, but, in consequence, the lack of that evaluative action can compromise Distance Higher Education. The methodology consisted of literature review, documentary review, use of secondary data from a project of institutional evaluation and, besides, a field research, developed by means of a case study. The data gathering was done by means of the application of an on-line survey, and interview with graduates, in order to gather data from their academic trajectory, their perception on the quality of the course, and their professional insertion in the work market. The theoretical framework involved the contributions of authors that investigate public policies for Higher Education in DL, considering the concepts of graduates and institutional evaluation. The results revealed data that contribute to the enhancement of educational management of Distance Higher Education, in order to grant higher quality for the projects implemented. In the egresses’ perception, the training received was enough for their insertion in the work market and afforded them better life quality, despite the infrastructure offered by the courses did not grant ideal conditions for the teaching-learning process.